Hydrogel, preparation method thereof and electronic skin

Through the double-layer hydrogel design, the existing electronic skin fixation methods are solved, and stable fixation, comfortable experience and self-healing functions are achieved, and it is suitable for intelligent health monitoring and human-computer interaction.

CN119391115APending Publication Date: 2025-02-07BEIJING ZENITHNANO TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411710523.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing methods for fixing electronic skin rely on tape or adhesives, resulting in complex, inconvenient use, and may cause skin allergies or discomfort, and are not firm enough to affect performance and accuracy.

Method used

A double-layer hydrogel design is adopted, where the first glue layer provides structural support and mechanical strength, and the second glue layer provides excellent adhesion and comfort, capable of firmly adhering to the surfaces of different substances, including the skin.

Benefits of technology

It realizes stable fixation of electronic skin, improves user comfort experience, simplifies the installation and disassembly process, avoids the discomfort caused by adhesives, and gives electronic skin self-healing and multiple sensing capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391115A_ABST
    Figure CN119391115A_ABST
Patent Text Reader

Abstract

The invention relates to hydrogel, a preparation method thereof and electronic skin, and relates to the technical field of gel, the hydrogel comprises a first glue layer and a second glue layer, the first glue layer comprises, by weight, 4-20 parts of a first high-molecular polymer, 2-10 parts of a first electrolyte, 30-35 parts of first polyol, and 45-52 parts of a first solvent; the weight ratio of the first polyol to the first solvent is 4: 6; the second adhesive layer is prepared from the following components in parts by weight: 1 to 3 parts of viscous material, 4 to 20 parts of second high-molecular polymer, 2 to 10 parts of second electrolyte, 8 to 9 parts of second polyhydric alcohol and 72 to 81 parts of second solvent; the weight ratio of the second polyol to the second solvent is 1: 9. According to the hydrogel disclosed by the invention, the design of the first adhesive layer and the second adhesive layer is utilized, so that the electronic skin can be kept adhered on one surface and is not adhered on the other surface, and the design can ensure that the electronic skin is firmly fixed; in addition, excellent flexibility and comfort are achieved, and extra adhesive tape or auxiliary tools are not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gel technology, and in particular to a hydrogel and a preparation method thereof, and electronic skin. Background Art

[0002] A humanoid robot, or humanoid robot, is a robot that mimics the appearance and functions of a human, with a design that includes two feet, two arms, and a head. This appearance enables humanoid robots to demonstrate excellent versatility and adaptability in various human working and living environments. It can adapt to the irregularities of the human environment and use tools like humans, achieving seamless integration with humans. In addition, the human appearance of humanoid robots increases public acceptance and plays an important role in human-computer interaction. By integrating multiple sensors, these robots can realize multiple perception functions such as vision, hearing, touch, and smell, thereby improving their ability to operate in complex environments.

[0003] Electronic skin is a flexible electronic device used in humanoid robots to simulate the perception and response functions of human skin. The widespread application demand of these electronic skins has driven the development of new fixing materials to improve the usage experience and performance. At present, the fixing methods of commonly used materials for electronic skin (silicone, PDMS, ECOFLEX, etc.) usually rely on tape or other adhesives, which increases the complexity and inconvenience of use. First, the use of tape or adhesives may cause skin allergies or discomfort; secondly, the use of tape may limit the flexibility and comfort of electronic skin; in addition, existing fixing methods may not be strong enough, causing the electronic skin to fall off or shift during use, affecting its performance and accuracy.

[0004] Therefore, a new fixing material is needed that can provide better comfort and stability and solve the shortcomings of the existing methods. Summary of the invention

[0005] In order to address the deficiencies in existing methods and provide better comfort and stability, the present application provides a hydrogel and a preparation method thereof, and electronic skin.

[0006] This application adopts the following technical solutions:

[0007] A hydrogel, comprising a first adhesive layer and a second adhesive layer, wherein the first adhesive layer comprises, by weight: 4-20 parts of a first high molecular polymer, 2-10 parts of a first electrolyte, 30-35 parts of a first polyol, and 45-52 parts of a first solvent; the weight ratio of the first polyol to the first solvent is 4:6;

[0008] The second adhesive layer comprises, by weight: 1-3 parts of adhesive material, 4-20 parts of a second high molecular polymer, 2-10 parts of a second electrolyte, 8-9 parts of a second polyol, and 72-81 parts of a second solvent; the weight ratio of the second polyol to the second solvent is 1:9.

[0009] By adopting the above-mentioned technical solution and utilizing the design of the first adhesive layer and the second adhesive layer, the electronic skin can remain adhered on one side while not adhered on the other side. This design can ensure that the electronic skin is firmly fixed. The first adhesive layer provides structural support and mechanical strength, while the second adhesive layer provides excellent adhesion and comfort, and can be attached to the surfaces of different materials such as glass and human skin. The hydrogel of the present application has excellent flexibility and comfort, and can provide a soft and comfortable touch when fitted to the skin. It uses a double-layer structure and does not require additional tape or auxiliary tools, thus avoiding the discomfort caused by adhesives commonly used in traditional methods and improving the user's comfort experience. In addition, the double-layer hydrogel design makes the installation and removal process simpler. The user only needs to directly fit the electronic skin without the need for other auxiliary tools or complicated operations, making the operation more convenient.

[0010] In a specific embodiment, the peeling force of the second adhesive layer is 50-150 g / cm.

[0011] By adopting the above technical solution and utilizing the above parameter design, sufficient adhesion can be provided to prevent falling off or shifting during use, thereby improving the overall stability and durability and maintaining its performance and effect.

[0012] In a specific embodiment, the viscous material is clay or polydopamine.

[0013] By adopting the above technical solutions, clay has good adhesion and stability, can form a strong fixation on the skin, and maintain consistent viscosity under temperature changes. Polydopamine can provide excellent adhesion, can adhere firmly to a variety of surfaces, and has excellent biocompatibility; this type of material can be easily attached and removed without leaving residual glue or causing damage to the skin, and the aging resistance of these two materials can extend the service life.

[0014] In a specific embodiment, the first high molecular polymer and the second high molecular polymer are polyvinyl alcohol.

[0015] By adopting the above technical solution and utilizing the above materials, good mechanical strength and stability can be provided, the device can withstand large external forces and stresses, and is suitable for application scenarios requiring flexibility and suitable for fitting to sensitive surfaces such as the skin. In actual design, by using the same polymer in the two adhesive layers, the consistency of the materials can be ensured, the production process can be simplified, and by adjusting the ratio of the polymer and other auxiliary materials, the performance of the two layers of hydrogel can be optimized to meet different application requirements.

[0016] In a specific embodiment, the first electrolyte and the second electrolyte are one or more of MgCl2, ZnCl2, and NaCl.

[0017] By adopting the above technical solution, MgCl2, ZnCl2 or NaCl is used as the electrolyte. 2+ 、Zn 2+ and Na + Ionic coordination bonds are formed between ions and functional groups in the hydrogel (such as carboxyl, phenolic hydroxyl, etc.). When the hydrogel is damaged or broken, these ionic bonds can be reformed to restore the overall structure and function of the material. The formation of ionic coordination bonds provides a self-healing mechanism, improves the long-term service life and reliability of the material, and enables it to perform well in various application scenarios; MgCl2, ZnCl2 and NaCl as electrolytes can increase the ionic conductivity of the hydrogel, and the improved ionic conductivity helps to achieve better response performance under the action of the electric field; and the increase in ionic coordination bonds significantly improves the mechanical strength and toughness of the hydrogel. When subjected to stress or damage, these ionic bonds can provide additional support and elasticity, reducing the crack propagation of the material.

[0018] In a specific embodiment, the first polyol and the second polyol are glycerol or polyethylene glycol.

[0019] By adopting the above technical solution and using glycerol and PEG as polyols, its flexibility, strength and moisturizing properties can be improved, the formation and processing process of the gel can be improved, the self-healing process can be promoted, and the repair ability of the material can be improved. By selecting different polyol combinations, the physical properties of the adhesive layer can be adjusted to meet specific needs.

[0020] In a specific embodiment, the first solvent and the second solvent are water.

[0021] By adopting the above technical solution, water as the main solvent provides the ability to dissolve and disperse the various component materials, ensuring that the two layers of hydrogel have a uniform structure and appropriate flexibility. By adjusting the proportion of water, the hardness and elasticity of the two layers of hydrogel can be controlled, and the softness and adhesion of the adhesive layer can be improved to meet different application requirements.

[0022] In a specific implementation manner, the thickness ratio of the first adhesive layer to the second adhesive layer is 1:1, and the mass ratio of the first adhesive layer to the second adhesive layer is 1:1.

[0023] By adopting the above technical solution, uniform thickness can avoid stress concentration and reduce the risk of structural defects or failure caused by uneven thickness; and the equal mass ratio helps to ensure uniform adhesion and interaction between the two layers, reducing possible delamination or peeling problems.

[0024] In a specific embodiment, the first adhesive layer has a tensile strength of 0.2-5 MPa, an elastic modulus of 0.05-1 MPa, and an elongation at break of 200-1000%.

[0025] By adopting the above technical solution, the above parameters can reflect that the first adhesive layer has good tensile resistance and can adapt to larger deformation without being easy to break; the lower elastic modulus ensures that the first adhesive layer has sufficient flexibility when subjected to stress, reducing the stress concentration problem; the high elongation at break indicates that the first adhesive layer can be significantly deformed when subjected to tension, thereby enhancing the durability and reliability of the structure.

[0026] In a specific embodiment, the hydrogel has a tensile sensitivity coefficient of 0.5-8 and a pressure sensitivity coefficient of 0.08-0.5 kPa. -1 .

[0027] By adopting the above technical solution, the hydrogel can respond quickly and accurately under tension and pressure, causing changes in resistance through shape changes, thereby achieving efficient strain and pressure sensitivity. This property makes the hydrogel very suitable for use in sensors and monitoring systems, and can sense and feedback external mechanical changes in real time, thereby improving the overall performance and reliability of the system.

[0028] In a specific embodiment, the temperature sensitivity coefficient of the hydrogel is 0.01-0.1°C -1 .

[0029] By adopting the above technical solution, the temperature sensitivity coefficient of the hydrogel is 0.01-0.1℃ -1 The range of , which means it is very sensitive to temperature changes. Temperature changes will cause changes in the ion migration rate in the hydrogel, thereby causing changes in resistance. Since the change in resistance is directly related to the temperature change, the hydrogel can provide accurate temperature perception and achieve a highly sensitive response to temperature.

[0030] A method for preparing a hydrogel, characterized in that it comprises the following steps:

[0031] S1, providing a mold, preparing 4-20 parts of a first high molecular polymer, 2-10 parts of a first electrolyte, 30-35 parts of a first polyol, and 45-52 parts of a first solvent, and mixing the above materials to form a first solution;

[0032] S2, heating the first solution at 80-90° C. for 20-50 min to dissolve, pouring into the mold, cooling to -25--15° C. and freezing for 24 h to form a first adhesive layer, taking out and placing at room temperature for 1 h;

[0033] S3, preparing 1-3 parts of a viscous material, 4-20 parts of a second high molecular polymer, 2-10 parts of a second electrolyte, 8-9 parts of a second polyol, and 72-81 parts of a second solvent, and mixing the above materials to form a second solution;

[0034] S4, heating the second solution at 80-90°C for 20-50 min to dissolve, pouring it onto the first adhesive layer in the mold, cooling it to -25-15°C and freezing it for 24 h to form a second adhesive layer, taking it out and placing it at room temperature for 1 h to obtain a double-layer hydrogel.

[0035] By adopting the above technical solution, the double-layer structure improves the mechanical strength and durability of the hydrogel; the different formulations of the first layer and the second layer give the hydrogel good strain, pressure-sensitive, and temperature-sensitive properties, enabling it to perform well in sensors and other smart materials. By adjusting the ratio of glycerol and water and selecting materials of different components, the physical and chemical properties of the hydrogel can be precisely controlled. Among them, the viscosity is increased by adding viscous materials (such as clay or polydopamine), allowing the hydrogel to fit closely to the skin without the need for additional tape, and giving the hydrogel self-healing properties, thereby improving the durability and long-term stability of the material to meet the needs of different applications.

[0036] An electronic skin comprises the hydrogel as described above.

[0037] By adopting the above-mentioned technical solution, the self-healing property of the hydrogel enables the electronic skin to return to its original state after being damaged, extending its service life and maintaining stable performance. By adding sticky materials, the electronic skin can fit tightly to the skin surface without the need for additional adhesive materials, thereby improving wearing comfort and stability. The double-layer structure enables the electronic skin to have temperature, pressure and stress sensing capabilities at the same time, and can accurately monitor and feedback environmental changes, making it suitable for high-tech applications such as smart health monitoring, flexible sensors and human-computer interaction.

[0038] To sum up, the beneficial technical effects of the present application are: the hydrogel of the present application can be used for electronic skin, and its self-healing properties enable the electronic skin to quickly recover to its original state after being damaged, thereby significantly extending its service life and maintaining stable performance; by adding sticky materials, the electronic skin can fit closely to the skin surface without the use of additional adhesives, which not only improves the wearing comfort but also enhances stability; its double-layer structure gives the electronic skin the ability to sense temperature, pressure and stress at the same time, enabling it to accurately monitor and feedback environmental changes; the hydrogel electronic skin has shown broad application prospects in high-tech fields such as intelligent health monitoring, flexible sensors, and human-computer interaction, and its superior self-healing ability and multiple sensing characteristics make it widely used in electronic skin technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of the hydrogel in the embodiment of the present application.

[0040] Explanation of reference numerals: 1, first adhesive layer; 2, second adhesive layer. DETAILED DESCRIPTION

[0041] The following is combined with Figure 1 This application is described in further detail.

[0042] Reference Figure 1 , the embodiment of the present application discloses a hydrogel, in this embodiment, the hydrogel includes but is not limited to being applied to electronic skin;

[0043] The hydrogel includes a first adhesive layer 1 and a second adhesive layer 2, the first adhesive layer 1 and the second adhesive layer 2 are stacked, and the first adhesive layer 1 and the second adhesive layer 2 are layers including but not limited to being prepared by layered coating;

[0044] The first adhesive layer 1 includes, by weight: 4-20 parts of the first high molecular polymer, 2-10 parts of the first electrolyte, 30-35 parts of the first polyol, and 45-52 parts of the first solvent; the weight ratio of the first polyol to the first solvent is 4:6; in this embodiment, preferably, the first high molecular polymer is 10 parts, the first electrolyte is 5 parts, the first polyol is 34 parts, and the first solvent is 51 parts;

[0045] The second adhesive layer 2 comprises, by weight: 1-3 parts of adhesive material, 4-20 parts of the second high molecular polymer, 2-10 parts of the second electrolyte, 8-9 parts of the second polyol, and 72-81 parts of the second solvent; the weight ratio of the second polyol to the second solvent is 1:9; in this embodiment, preferably, 2 parts of adhesive material, 10 parts of the second high molecular polymer, 5 parts of the second electrolyte, 8.2 parts of the second polyol, and 73.8 parts of the second solvent;

[0046] Through the above-mentioned ratio design, the first adhesive layer 1 provides structural support and mechanical strength, while the second adhesive layer 2 provides excellent adhesion and comfort, and can be attached to the surfaces of different materials such as glass, human skin, and electronic skin; this double-layer hydrogel design can provide good mechanical properties and efficient adhesion in a variety of applications, and has high conductivity, high sensitivity, excellent flexibility and self-healing ability, thereby improving the overall functionality and user experience of the product;

[0047] The peeling force of the second adhesive layer 2 is 50-150 g / cm; thus, sufficient adhesion can be provided to prevent the device from falling off or shifting during use, thereby improving overall stability and durability and maintaining its performance and effect;

[0048] The hydrogel of the present application is designed with a first adhesive layer 1 and a second adhesive layer 2 so that the electronic skin can remain adhered on one side while not adhered on the other side. This design can ensure that the electronic skin is firmly fixed, and the peeling force of 50-150g / cm ensures that the adhesion strength of the hydrogel is strong enough to prevent it from falling off, and can be easily torn off when needed; the double-layer hydrogel design makes the installation and removal process simpler, and the user only needs to directly fit the electronic skin without other auxiliary tools or complicated operations, which makes the operation more convenient; and the hydrogel of the present application has excellent flexibility and comfort, and can provide a soft and comfortable touch when fitted to the skin. It uses a double-layer structure and does not require additional tape or auxiliary tools, avoiding the discomfort caused by adhesives commonly used in traditional methods, improving the user's comfort experience, and can adapt to a variety of application requirements, thereby improving its performance and effects in actual applications.

[0049] The sticky material is clay or polydopamine; clay has good adhesion properties and can provide stable adhesion on various surfaces. Its adhesive layer can effectively maintain the position of the hydrogel and reduce sliding or falling off. By adjusting the type and concentration of clay, the peeling force of the adhesive layer can be precisely controlled to meet different application requirements. The addition of clay can also improve the structural stability and mechanical strength of the hydrogel. Clay is usually low in price, which can reduce material costs and is suitable for large-scale production.

[0050] Polydopamine is a self-healing material that can repair tiny damage during use, thereby improving the durability and stability of the adhesive layer. Polydopamine has extremely strong adhesion ability and excellent biocompatibility, and can be firmly attached to various surfaces, including biological tissues and medical equipment. Polydopamine has good adaptability to changes in humidity and temperature and can maintain stable adhesion properties under different environmental conditions; these two materials can be easily attached and removed without leaving residual glue or causing damage to the skin, and the aging resistance of these two materials can extend the service life.

[0051] The thickness ratio of the first adhesive layer 1 to the second adhesive layer 2 is 1:1. The uniform thickness can avoid stress concentration and reduce the risk of structural defects or failure caused by uneven thickness. The mass ratio of the first adhesive layer 1 to the second adhesive layer 2 is 1:1. The uniform mass ratio helps to ensure uniform adhesion and interaction between the two layers and reduce possible delamination or peeling problems.

[0052] In this embodiment, preferably, the first high molecular polymer and the second high molecular polymer are polyvinyl alcohol (PVA); polyvinyl alcohol can provide good mechanical strength and stability, can withstand large external forces and stresses, and is suitable for application scenarios requiring flexibility, and is suitable for fitting sensitive surfaces such as skin; in actual design, by using the same high molecular polymer in the two adhesive layers, the consistency of the materials can be ensured, the production process can be simplified, and by adjusting the ratio of the high molecular polymer and other auxiliary materials, the performance of the two layers of hydrogel can be optimized to meet different application requirements;

[0053] In this embodiment, auxiliary materials can be added to the first high molecular polymer and the second high molecular polymer to increase the mechanical strength of the hydrogel. The auxiliary materials can be but are not limited to modified polyurethane, polyvinyl pyrrolidone (PVP) and sodium carboxymethyl cellulose (CMC). The addition of modified polyurethane, polyvinyl pyrrolidone (PVP) and sodium carboxymethyl cellulose (CMC) can limit the free movement of polyvinyl alcohol (PVA) chain segments and reduce their slippage under stress, thereby improving the tensile strength and compressive strength of the material; wherein, the modified polyurethane can form a cross-linked network, enhance the structural strength of the material, and improve High durability and stability, the cross-linked structure can effectively prevent the slippage of chain segments, thereby improving the tensile strength; polyvinyl pyrrolidone (PVP), as a water-soluble polymer, can increase the interaction between polymer chains, and its molecular structure helps to form hydrogen bonds, improve the cohesion of the material, thereby improving the toughness of the hydrogel and making it less likely to break when stretched and bent; sodium carboxymethyl cellulose (CMC) has good hydrophilicity, can absorb water, form a viscous solution in water, and increase the viscosity of the hydrogel, thereby providing better support and stability for the material, thereby improving the flexibility and compressive strength of the material.

[0054] In this embodiment, the polyvinyl alcohol (PVA) of the second high molecular polymer can also be replaced by polyacrylic acid (PAA). Polyacrylic acid (PAA) is a soft polymer with good viscosity. Although its mechanical strength is lower than that of polyvinyl alcohol (PVA), it has good self-healing properties and can self-repair through its own physical and chemical properties after being damaged. Among them, the carboxylic acid group in polyacrylic acid can form a coordination bond with the divalent or trivalent ions in the second electrolyte, which has a certain reversibility. When the material is damaged by external force, the bond can be partially broken, but after the pressure is released, the bond will be reformed, thereby promoting the self-healing of the material; and the coordination bond formed by polyacrylic acid and the ion will give the glue a certain mechanical strength. At the same time, when it is partially damaged, the material can have better self-healing performance, thereby extending the service life of the material and reducing maintenance costs;

[0055] The carboxylic acid groups contained in polyacrylic acid (PAA) can effectively combine with divalent or trivalent ions in the second electrolyte to form a stable cross-linked structure through ionic bonds or coordination. The formation of such cross-links increases the interaction force between molecules and enhances the overall structural stability of the material. Moreover, these cross-links can be partially broken after being damaged. When the external conditions (such as temperature and humidity) are suitable, these cross-links can be formed again to enhance the integrity of the material. In addition, the sticky polyacrylic acid (PAA) is used as the second high molecular polymer. Its sticky characteristics can effectively improve the adhesion performance of the second adhesive layer 2, so that it exhibits stronger adhesion when the layers are combined. Moreover, unlike polyvinyl alcohol (PVA) which needs to be cross-linked under freezing conditions, polyacrylic acid (PAA) can undergo cross-linking reactions with divalent or trivalent ions in the second electrolyte at room temperature, which simplifies the preparation process and improves the convenience of operation.

[0056] The first electrolyte and the second electrolyte are one or more of MgCl2, ZnCl2, and NaCl; by using MgCl2, ZnCl2 or NaCl as the electrolyte, Mg 2+ 、Zn 2+ and Na + Ionic coordination bonds are formed between ions and functional groups in the hydrogel (such as carboxyl, phenolic hydroxyl, etc.). When the hydrogel is damaged or broken, these ionic bonds can be reformed to restore the overall structure and function of the material. The formation of ionic coordination bonds provides a self-healing mechanism, improves the long-term service life and reliability of the material, and enables it to perform well in various application scenarios; MgCl2, ZnCl2 and NaCl as electrolytes can increase the ionic conductivity of the hydrogel, and the improved ionic conductivity helps to achieve better response performance under the action of the electric field; and the increase in ionic coordination bonds significantly improves the mechanical strength and toughness of the hydrogel. When subjected to stress or damage, these ionic bonds can provide additional support and elasticity, reducing the crack propagation of the material.

[0057] The first polyol and the second polyol are glycerol or polyethylene glycol; glycerol can provide better flexibility and moisturizing effect, making the hydrogel softer, suitable for applications requiring high elasticity, and can enhance the softness and plasticity of the hydrogel, suitable for applications in contact with the skin; polyethylene glycol can improve the transparency and fluidity of the hydrogel, can improve the formation and processing process of the gel, and can improve the stability and durability of the hydrogel, increasing its performance in long-term use; by using glycerol and polyethylene glycol as polyols, its flexibility, strength and moisturizing can be improved, the formation and processing process of the gel can be improved, and the self-healing process can be promoted, and the repair ability of the material can be improved. By selecting different polyol combinations, the physical properties of the adhesive layer can be adjusted to meet specific needs.

[0058] The first solvent and the second solvent are water; water as the main solvent provides the ability to dissolve and disperse the various component materials, ensuring that the two layers of hydrogel have a uniform structure and appropriate flexibility. By adjusting the proportion of water, the hardness and elasticity of the two layers of hydrogel can be controlled, and the softness and adhesion of the adhesive layer can be improved to meet different application requirements.

[0059] In this embodiment, the tensile strength of the first adhesive layer 1 is 0.2-5MPa, the elastic modulus is 0.05-1MPa, and the elongation at break is 200-1000%; the above parameters can reflect that the first adhesive layer 1 has good tensile resistance and can adapt to large deformation without being easy to break; the lower elastic modulus ensures that the first adhesive layer 1 has sufficient flexibility when subjected to stress, reducing the stress concentration problem; the high elongation at break indicates that the first adhesive layer 1 can be significantly deformed when subjected to tension, thereby enhancing the durability and reliability of the structure.

[0060] In this embodiment, the tensile sensitivity coefficient of the hydrogel is 0.5-8, and the pressure sensitivity coefficient is 0.08-0.5 kPa. -1 ; This allows the hydrogel to respond quickly and accurately under tension and pressure, causing changes in resistance through shape changes, thereby achieving efficient strain and pressure sensitivity. This property makes the hydrogel very suitable for use in sensors and monitoring systems, which can sense and feedback external mechanical changes in real time, improving the overall performance and reliability of the system.

[0061] The temperature sensitivity coefficient of the hydrogel is 0.01-0.1℃ -1 ; This parameter shows that the hydrogel is very sensitive to temperature changes. When the ambient temperature changes, it will cause the Mg in the hydrogel to 2+ 、Zn 2+ 、Na + Changes in ion migration rate lead to changes in resistance. Since the change in resistance is directly related to temperature changes, hydrogels can provide accurate temperature perception and achieve a highly sensitive response to temperature.

[0062] The hydrogel of the present application can be used for electronic skin, and its self-healing properties enable the electronic skin to quickly recover to its original state after being damaged, thereby significantly extending its service life and maintaining stable performance; by adding sticky materials, the electronic skin can fit closely to the skin surface without the use of additional adhesives, which not only improves the wearing comfort but also enhances stability; its double-layer structure gives the electronic skin the ability to sense temperature, pressure and stress at the same time, enabling it to accurately monitor and feedback environmental changes; the hydrogel electronic skin has shown broad application prospects in high-tech fields such as intelligent health monitoring, flexible sensors and human-computer interaction, and its superior self-healing ability and multiple sensing properties make it widely used in electronic skin technology.

[0063] The present application also provides a method for preparing a hydrogel, including but not limited to layered coating and freeze-thaw cross-linking technology, the method comprising the following steps:

[0064] S1. Provide a mold and ensure that the required mold has been prepared, clean and dry. The shape and size of the mold should be consistent with the requirements of the final hydrogel;

[0065] Prepare 4-20 parts of the first high molecular polymer, 2-10 parts of the first electrolyte, 30-35 parts of the first polyol, and 45-52 parts of the first solvent; in the present embodiment, preferably, prepare 10 parts of the first high molecular polymer, 5 parts of the first electrolyte, 34 parts of the first polyol, and 51 parts of the first solvent, and mix them to form a first solution; specifically, in a suitable container, first add the first solvent and stir evenly, then gradually add the first high molecular polymer, the first electrolyte, and the first polyol, ensuring that each component is fully dissolved and mixed evenly, and continue stirring until all the components are evenly mixed to obtain a homogeneous first solution;

[0066] In this embodiment, the first high molecular polymer includes but is not limited to polyvinyl alcohol, the first electrolyte includes but is not limited to one or more of MgCl2, ZnCl2, and NaCl, the first polyol includes but is not limited to glycerol or polyethylene glycol, and the first solvent includes but is not limited to water.

[0067] S2, heat the first solution at 80-90°C for 20-50 min to dissolve, pour into a mold, cool to -25--15°C and freeze for 24 h, take out and place at room temperature for 1 h;

[0068] In this embodiment, preferably, the first solution is heated at 85° C. for 30 min to dissolve, so that all components are completely dissolved and evenly mixed, poured into a mold, and then cooled to -20° C. and frozen for 24 h to form a physically cross-linked first adhesive layer 1 by freeze-thawing, and then taken out and placed at room temperature for 1 h;

[0069] Specifically, the prepared first solution is placed in a heating device (such as a water bath, a thermostatic stirrer, etc.), the temperature is set to 85°C, and heated and stirred for 30 minutes to ensure that all ingredients are completely dissolved and evenly mixed, and the uniformity of the solution is checked regularly to ensure that there are no precipitated or undissolved particles; the heated first solution is carefully poured into the prepared mold, and bubbles and impurities are avoided as much as possible to ensure the quality of the final product; the mold containing the first solution is gradually cooled to -20°C. This process can be completed using a freezing device or a refrigeration device, and is frozen at -20°C for 24 hours to allow the first solution to form a physically cross-linked first adhesive layer 1 through a freeze-thaw process. This process can enhance the structural stability and mechanical properties of the material; the mold is removed from the freezing device, and placed at room temperature for 1 hour to allow it to return to room temperature to further stabilize its physical properties, and the cured first adhesive layer 1 is checked to ensure that its physical cross-linking effect is good and the surface is smooth and defect-free.

[0070] S3, preparing 1-3 parts of viscous material, 4-20 parts of the second high molecular polymer, 2-10 parts of the second electrolyte, 8-9 parts of the second polyol, and 72-81 parts of the second solvent; in this embodiment, preferably, preparing 2 parts of viscous material, 10 parts of the first high molecular polymer, 5 parts of the first electrolyte, 8.2 parts of the first polyol, and 73.8 parts of the first solvent, and mixing them to form a second solution;

[0071] Specifically, in a suitable container, first add the first solvent and stir evenly, then gradually add the first high molecular polymer, the first electrolyte and the first polyol, ensure that each component is fully dissolved, add 2 parts of viscous material, and continue stirring until all components are evenly mixed to obtain a homogeneous second solution;

[0072] In this embodiment, the viscous material includes but is not limited to clay or polydopamine, the second high polymer includes but is not limited to polyvinyl alcohol, the second electrolyte includes but is not limited to one or more of MgCl2, ZnCl2, and NaCl, the second polyol includes but is not limited to glycerol or polyethylene glycol, and the second solvent includes but is not limited to water.

[0073] S4, heating the second solution at 80-90°C for 20-50 min to dissolve, pouring it onto the first adhesive layer 1 in the mold, cooling it to -25-15°C and freezing it for 24 h to form a second adhesive layer 2, taking it out and placing it at room temperature for 1 h to obtain a double-layer hydrogel;

[0074] In this embodiment, preferably, the second solution is heated at 85° C. for 30 min to dissolve, so that all components are completely dissolved and evenly mixed, poured onto the first adhesive layer 1 in the mold, and then cooled to -20° C. and frozen for 24 h to form a physically cross-linked second adhesive layer 2 by freeze-thawing, and then taken out and placed at room temperature for 1 h to obtain a double-layer hydrogel;

[0075] Specifically, the prepared second solution is placed in a heating device (such as a water bath, a thermostatic stirrer, etc.), the temperature is set to 85°C, heated and stirred for 30 minutes, ensuring that all ingredients are completely dissolved and evenly mixed, and the uniformity of the solution is checked regularly to ensure that there are no precipitated or undissolved particles; the heated first solution is carefully poured onto the first adhesive layer 1 in the prepared mold to ensure uniform coverage and try to avoid mixing of bubbles and impurities to ensure the quality of the final product; the mold containing the second solution is gradually cooled to -20°C. A freezing device or a refrigeration device can be used to complete this process. Freeze at -20°C for 24 hours to allow the first solution to form a physically cross-linked second adhesive layer 2 through a freeze-thaw process. This process can enhance the structural stability and mechanical properties of the material; remove the mold from the freezing device, place it at room temperature for 1 hour, let it return to room temperature, further stabilize its physical properties, and obtain a double-layer hydrogel; check the structure and properties of the solidified double-layer hydrogel to ensure that the cross-linking effect between the two layers is good and the surface is smooth and defect-free.

[0076] In this embodiment, the hydrogel prepared by the above method includes but is not limited to being applied to electronic skin;

[0077] The double-layer hydrogel prepared by this method has the following characteristics: one side is adhesive and the other side is non-adhesive, it has self-healing ability, and it responds to temperature, pressure and stress at the same time. The sensor of this hydrogel shows excellent mechanical test performance and stability, high sensitivity and good repeatability, the preparation method is simple, and the material source is easy to obtain and low in price. This hydrogel can be used to monitor human physiological signals and body temperature, and has broad application prospects in the application of flexible electronic skin, especially in humanoid robots.

[0078] This method prepares a double-layer hydrogel through layered coating and freeze-thaw cross-linking technology. The double-layer structure improves the mechanical strength and durability of the hydrogel. The different formulations of the first layer and the second layer give the hydrogel good strain, pressure sensitivity, and temperature sensitivity, enabling it to perform well in sensors and other smart materials. The physical and chemical properties of the hydrogel can be precisely controlled by adjusting the ratio of glycerol and water and selecting materials of different components. Among them, the viscosity is increased by adding viscous materials (such as clay or polydopamine), allowing the hydrogel to fit closely to the skin without the need for additional tape, and giving the hydrogel self-healing properties, thereby improving the durability and long-term stability of the material to meet different application requirements.

[0079] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A hydrogel, characterized in that: It comprises a first adhesive layer and a second adhesive layer, wherein the first adhesive layer comprises, by weight: 4-20 parts of a first high molecular polymer, 2-10 parts of a first electrolyte, 30-35 parts of a first polyol, and 45-52 parts of a first solvent; the weight ratio of the first polyol to the first solvent is 4:6; The second adhesive layer comprises, by weight: 1-3 parts of adhesive material, 4-20 parts of a second high molecular polymer, 2-10 parts of a second electrolyte, 8-9 parts of a second polyol, and 72-81 parts of a second solvent; the weight ratio of the second polyol to the second solvent is 1:

9.

2. The hydrogel according to claim 1, characterized in that: The peeling force of the second adhesive layer is 50-150 g / cm.

3. The hydrogel according to claim 1, characterized in that: The viscous material is clay or polydopamine.

4. The hydrogel according to claim 1, characterized in that: The first high molecular polymer and the second high molecular polymer are polyvinyl alcohol.

5. The hydrogel according to claim 1, characterized in that: The first electrolyte and the second electrolyte are one or more of MgCl2, ZnCl2, and NaCl.

6. The hydrogel according to claim 1, characterized in that: The first polyol and the second polyol are glycerol or polyethylene glycol.

7. The hydrogel according to claim 1, characterized in that: The first solvent and the second solvent are water.

8. The hydrogel according to claim 1, characterized in that: The thickness ratio of the first adhesive layer to the second adhesive layer is 1:1, and the mass ratio of the first adhesive layer to the second adhesive layer is 1:

1.

9. The hydrogel according to claim 1, characterized in that: The tensile strength of the first adhesive layer is 0.2-5 MPa, the elastic modulus is 0.05-1 MPa, and the elongation at break is 200-1000%.

10. The hydrogel according to claim 1, characterized in that: The hydrogel has a tensile sensitivity coefficient of 0.5-8 and a pressure sensitivity coefficient of 0.08-0.5 kPa -1 .

11. The hydrogel according to claim 1, characterized in that: The temperature sensitivity coefficient of the hydrogel is 0.01-0.1°C -1 .

12. A method for preparing a hydrogel, characterized in that: The following steps are involved: S1, providing a mold, preparing 4-20 parts of a first high molecular polymer, 2-10 parts of a first electrolyte, 30-35 parts of a first polyol, and 45-52 parts of a first solvent, and mixing the above materials to form a first solution; S2, heating the first solution at 80-90° C. for 20-50 min to dissolve, pouring into the mold, cooling to -25--15° C. and freezing for 24 h to form a first adhesive layer, taking out and placing at room temperature for 1 h; S3, preparing 1-3 parts of a viscous material, 4-20 parts of a second high molecular polymer, 2-10 parts of a second electrolyte, 8-9 parts of a second polyol, and 72-81 parts of a second solvent, and mixing the above materials to form a second solution; S4, heating the second solution at 80-90°C for 20-50 min to dissolve, pouring it onto the first adhesive layer in the mold, cooling it to -25-15°C and freezing it for 24 h to form a second adhesive layer, taking it out and placing it at room temperature for 1 h to obtain a double-layer hydrogel.

13. An electronic skin, characterized in that: The invention comprises the hydrogel according to any one of claims 1 to 11 or the hydrogel obtained by the preparation method according to claim 12.